Social Interaction of PUBG Mobile Gamers in the "Eden Esports" Community from A Dramaturgic Perspective - Haryadi, Rofiq Noorman (COMMUSTY Journal of Communication Studies and Society, 2023)
Traditional games are becoming outmoded and rarely used. Technology has transformed conventional games, making online games more engaging. PUBG Mobile is a popular internet game among teens. Social interaction concerns can arise in gaming, especially when one team or opponents is verbally attacked with criticism, insults, and humiliations. Players often criticise, criticise, and degrade teams and opponents in community participation and gaming. Dramaturgical analysis is used to evaluate Pubg Mobile Gamers' social interactions in the "Eden Esports" group. This study uses a qualitative descriptive research strategy. This study included interviews, observation, and documentation with ten informants. This study found that gamers use disparaging language and slurs. This contrasts with their domestic or non-community behaviour, when they speak less and do less. Completed. Goffman believes that direct interpersonal exchanges involve dramatic components. Individuals choose a character and expose it to appropriate situations and discussion partners.